Evaluation of the Performance of Steel in Reinforced Concrete by Electrochemical Methods - Manea, Enas M.; Hammadi, Nawal J.; Ali, Dhia C. (Basrah Journal for Engineering Sciences, 2014)
The effect of different dosages of the high range water reducing admixture–additive- (HRWRA), the commercially polymeric material (Plastocrete-N), on the corrosion resistance of embedded steel in concrete exposed to chloride solution in the absence and presence of sulfate ions was studied. In the present study, four levels of polymeric material (Plastocrete-N) (0.125%, 0.250%, 0.375%, and 0.500% by weight of cement) were used to prepare HRWRA treated concrete. The concrete specimens exposed to chloride and chloride–sulfate solutions at concentrations of (3.5% NaCl and 5% Na2SO4), at ambient temperature. The electrochemical behavior of steel in both reference and HRWRA concretes was studied under the effect of corrosive environments using corrosion measurement systems such as: a) half – cell potentials measurement system and b) accelerated corrosion test system. The results showed that a longer time of corrosion initiation (180 day) observed with 0.500% HRWRA containing concrete compared to other different HRWRA percentage including the reference concrete. It was concluded that the use of 0.500% HRWRA provided superior protection to steel reinforcement in concrete that subjected to corrosive environments. Furthermore, the steel with 0.500% HRWRA was subjected to corrosion test by mass loss, it is evident that a reduction in mass loss by about 90.2% and 85.2% in both solutions, respectively.